IoT projects with NVIDIA Jetson Nano : AI-enabled Internet of Things projects for beginners - Kurniawan, Agus, 1984- (Apress, 2021)
Explore the capabilities of the NVIDIA Jetson Nano, an IoT device designed to perform computations like a computer desktop. This book will show you how to build your first project and optimize your devices, programs, and daily activities with the AI computation abilities of the Jetson Nano. This board consists of CPU Quad-core ARM A57 @ 1.43 GHz and GPU 128-core Maxwell. With this hardware specification, the board can run multiple neural networks in parallel for complex AI applications. With the integrated sensor and actuators, this board enables stronger IoT solutions and provides more advanced capabilities. Discover how develop complex IoT projects with the Jetson Nano today. You will: Set up NVIDIA Jetson Nano device Build applications like image classification, object detection, segmentation, and speech processing Use the Jetson Nano to process daily computer activities such as browsing the internet, checking emails, or playing music and videos Implement machine learning computations into your projects.